The Definitive Diagnosis of Tuberculous Meningitis (TBM) di RSUP dr. Kariadi Semarang Descriptive study in adult patients using IS6110-based PCR amplification for detecting Mycobacterium tuberculosis - Masfiyah, Masfiyah; Bintoro, Aris Catur; Hadi, Purnomo (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
Tuberculous meningitis (TBM) is the most common cause of central nervous system infection and has very high morbidity and mortality. The definitive diagnosis of TBM in RSUP dr Kariadi Semarang has been insufficient. This study aimed at finding out the definitive diagnosis of TBM di RSUP dr Kariadi Semarang using IS6110 sensitive and specific primer. This was a descriptive study included all in-patients with meningitis and/or TBM of RSUP Dr Kariadi Semarang aged > 14 years with Thwaites’ Diagnostic Score ≤ 4 between March 1, 2013 and November, 30 2013. The devinitive diagnosis of TBM was made using IS6110-based PCR amplification for detecting Mycobacterium tuberculosis complex conducted in microbiology clinic of FK UNDIP/RSUP dr. Kariadi Semarang. The secondary data was the basic and laboratory data from the medical records of the patients. Mean age was 39.59 ± 15.7. Six (35.3%) pasients were diagnosed with devinitive TBM, 3 (17.64%) were meningitis positive by NTM (Non Tuberculous Mycobacteria). Dual infection was found in 1 (5.8%) case between TBM and bacterial meningitis. Most patients were productive age. Some had devititive TBM. The pasient with meningitis and dual infection were also diagnosed with NTM (Non Tuberculous Mycobacteria).